A Dyson sphere around a black hole. Issue 2 (1st July 2021) - Hsiao, Tiger Yu-Yang; Goto, Tomotsugu; Hashimoto, Tetsuya; Santos, Daryl Joe D; On, Alvina Y L; Kilerci-Eser, Ece; Wong, Yi Hang Valerie; Kim, Seong Jin; Wu, Cossas K-W; Ho, Simon C-C; Lu, Ting-Yi
ABSTRACT: The search for extraterrestrial intelligence (SETI) has been conducted for nearly 60 yr. A Dyson sphere, a spherical structure that surrounds a star and transports its radiative energy outwards as an energy source for an advanced civilization, is one of the main targets of SETI. In this study, we discuss whether building a Dyson sphere around a black hole is effective. We consider six energy sources: (i) the cosmic microwave background, (ii) the Hawking radiation, (iii) an accretion disc, (iv) Bondi accretion, (v) a corona, and (vi) relativistic jets. To develop future civilizations (for example, a Type II civilization), 4× 10^26 W(1 L_) is expected to be needed. Among (iii) to (vi), the largest luminosity can be collected from an accretion disc, reaching 10^5 L_, enough to maintain a Type II civilization. Moreover, if a Dyson sphere collects not only the electromagnetic radiation but also other types of energy (e.g. kinetic energy) from the jets, the total collected energy would be approximately 5 times larger. Considering the emission from a Dyson sphere, our results show that the Dyson sphere around a stellar-mass black hole in the Milky Way (10 kpc away from us) is detectable in the ultraviolet (10-400 nm), optical (400-760 nm), near-infrared (760 nm-5 μ m ), and mid-infrared (5-40 μ m ) wavelengths via the waste heat radiation using current telescopes such as Galaxy Evolution Explorer Ultraviolet Sky Surveys. Performing model fitting to observed spectral energy distributions and measuring the variability of radial velocity may help us to identify these possible artificial structures.